Application of Inorganic Fertilizer on 8 Varieties of Red Chili (Capsicum annum L) in the Lowlands - Hendra Purnama Afniawan (Contributions of Central Research Institute for Agriculture, 2021)
The purpose of this study was to determine the productivity of eight varieties of large red chili (Capsicum annum L) against fertilization levels grown inorganically in the lowlands. Observations made in this study included non-destructive, destructive and harvest observations. Among others: Number of branches per plant, plant height, number of leaves, number of flowers, number of fruit, fruit set, for destructive observation is the measurement of leaf area, while for harvest observation: fresh weight of fruit planted, fresh weight of fruit per plot, number of fruit per plant, fruit size, number of fruit that are attacked by pests. Analysis of the observed data used analysis of variance (F count). If there were significant differences between the treatments, a Least Significant Difference (LSD) test was carried out with an error rate of 5%. Based on the research results from observational data, it shows that several doses of inorganic fertilizers on 8 large chili cultivars did not produce any interactions. Likewise with the use of inorganic fertilizers with large chili cultivars with doses of P1: Urea 100kg ha-1 + Sp-36 150 kg ha-1, P2: Urea 175 kg ha-1 + Sp-36 300 kg ha-1, and P3: Urea 250 kg kg ha-1 + Sp-36 450 kg ha-1 had no effect on the various observed variables. Significant effect was obtained from the use of various varieties of chili peppers. These significantly different responses were shown by the variable plant height, production per plant and yield components. Based on plant height observation data up to 84 hst, Jet set had the highest height compared to the other cultivars, which was 32.13% higher than Horizon cultivar. Meanwhile, based on yield component data, the Horizon cultivar produced the highest yield, which was 6.96 ton.ha-1, while the lowest was produced by the Hot Chili cultivar, which was 1.66 ton.ha-1.